2010
DOI: 10.1007/s10592-010-0065-0
|View full text |Cite
|
Sign up to set email alerts
|

Endangered species in small habitat patches can possess high genetic diversity: the case of the Tana River red colobus and mangabey

Abstract: We used mtDNA sequence data from the Tana River red colobus and mangabey to determine how their population genetic structure was influenced by dispersal and habitat fragmentation. The colobus and mangabey are critically endangered primates endemic to gallery forests in eastern Kenya. The forests are a Pliocene-Pleistocene refugium that has recently undergone significant habitat loss and fragmentation due to human activities. We expected both primates to exhibit low levels of genetic diversity due to elevated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 49 publications
(65 reference statements)
1
10
0
Order By: Relevance
“…Little is known about African colobine population genetic diversity and structure. The studies conducted so far have focused only on few colobus populations from eastern Africa (Harris et al, 2009; McDonald and Hamilton, 2010; Mbora and McPeek, 2010). Harris et al (2009) used both observational and genetic data to describe the complex dispersal system of a Colobus guereza population in Uganda, where the genetic structure of social groups is shaped by male‐mediated gene flow together with less common episodes of female dispersal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about African colobine population genetic diversity and structure. The studies conducted so far have focused only on few colobus populations from eastern Africa (Harris et al, 2009; McDonald and Hamilton, 2010; Mbora and McPeek, 2010). Harris et al (2009) used both observational and genetic data to describe the complex dispersal system of a Colobus guereza population in Uganda, where the genetic structure of social groups is shaped by male‐mediated gene flow together with less common episodes of female dispersal.…”
mentioning
confidence: 99%
“…McDonald and Hamilton (2010) examined the genetic diversity and phylogenetic relationships among Kenyan and Tanzanian Colobus angolensis palliatus populations. Only one study on red colobus ( Piliocolobus badius rufomitratus ) has been reported from the Tana River in Kenya, which evaluated mitochondrial diversity within this population (Mbora and McPeek, 2010).…”
mentioning
confidence: 99%
“…However, the extent to which habitat fragmentation has a negative effect on the genetic structure and persistence of animal populations remains debated [6]. While some studies have demonstrated a pronounced effect of habitat fragmentation on species' population genetic structure (e.g., [7][8][9][10][11][12]), others have failed to detect these effects (e.g., [11,[13][14][15]). In this context, a better understanding of how and the degree to which fragmentation affects species will help to understand demographic processes that are triggered by fragmentation events.…”
Section: Introductionmentioning
confidence: 99%
“…This condition becomes a serious note for conservationists. Miangas Island as a small habitat will affect genetic flow, genetic drift, and fitness and become a factor against extinction rate especially for endangered species (Mbora and McPeek 2010).…”
Section: Introductionmentioning
confidence: 99%